Developmental Patterns of a Child with Autism Spectrum Disorder at General Hospital Of Bondowoso District - Nisa, Elsa Zahrotun; Putri, Ellyana Ilsan Eka (Universitas Muhammadiyah Sidoarjo, 2024)
This article discusses the development of a 5-year-old child with mild Autism Spectrum Disorder at General Hospital of Bondowoso District. The study aims to explore the child's developmental, daily challenges faced by a child with ASD, and the therapies implemented. The method used in this research is descriptive qualitative method. The data collection in this study used documentation, direct observation of the subject and interviews with the subject’s parents. The result shows an explanation of the symptoms that emerge during the subject's developmental stages. The subject shows delayed speech development, difficulty in forming long sentences, limited social skills, unable to stay still and often moving actively, as well as poor fine motor skills. Additionally, the subject also shows improvement or a prognosis towards a better outcome during therapy.